1984
DOI: 10.3109/02713688409000835
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry of mouse and human retina with antisera to insulin and S-100 protein

Abstract: Immunocytochemistry using peroxidase antiperoxidase (PAP) techniques showed insulin-like immunoreactivity in the human retina, and in the mouse retina and optic nerve. The immunoreaction product was seen in the inner nuclear, ganglion cell, outer and inner plexiform layers of the retinas, and in glial cell bodies of the optic nerve. A similar staining pattern using antiserum to S-100 protein, a marker for glial elements, was also seen in these tissues. This demonstrates that insulin or insulin-like immunoreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 14 publications
2
18
0
1
Order By: Relevance
“…Although it appears that insulin is unable to cross the blood-retinal barrier [19], the retina is capable of synthesizing insulin [20]; in situ hybridization and RT-PCR show that Müller cells contain mRNA for the prepro form of insulin [21,22]; and insulin and insulinlike immunoreactivity have been demonstrated throughout the retina, particularly in Müller cells [23]. Insulin levels in blood and various tissues are reported to range from 0.3 to 3.0 nM [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although it appears that insulin is unable to cross the blood-retinal barrier [19], the retina is capable of synthesizing insulin [20]; in situ hybridization and RT-PCR show that Müller cells contain mRNA for the prepro form of insulin [21,22]; and insulin and insulinlike immunoreactivity have been demonstrated throughout the retina, particularly in Müller cells [23]. Insulin levels in blood and various tissues are reported to range from 0.3 to 3.0 nM [24].…”
Section: Discussionmentioning
confidence: 99%
“…40 In these studies, using insulin antibodies in rodent retinal glial cells, Das found that these cells could produce insulin and that insulin receptors were present in glial cells, likely Müller cells. 40 From these initial studies, recent results have further suggested that receptors for insulin are present in the eye, specifically the retina. [41][42][43][44] Further studies by found the presence of the precursor of insulin, preproinsulin, in mRNA from an intact rat retina.…”
Section: Role Of Insulin Receptor Signaling In Retinamentioning
confidence: 99%
“…37,39 Following insulin stimulation, phosphorylation of Akt on Ser 473 will occur downstream of the IRS complexes to inhibit apoptosis. Das et al (1984) suggested the possibility of insulin being produced in other tissues beyond the beta cells of the pancreas. 40 In these studies, using insulin antibodies in rodent retinal glial cells, Das found that these cells could produce insulin and that insulin receptors were present in glial cells, likely Müller cells.…”
Section: Role Of Insulin Receptor Signaling In Retinamentioning
confidence: 99%
See 2 more Smart Citations